Artificial intelligence model in the cognitive and learning activities of university subjects - Abishev, N.; Ramazanov, R.; Abaideldanova, M.; Chesnokova, K.; Baizhumayeva, A. (Frontiers in Education, 2025)
This article examines the role of artificial intelligence (AI) models in the cognitive and learning activities of subjects in higher education institutions. The authors design this model using algorithms–sets of rules that enable programs to make decisions, recognize patterns, and generate predictions based on input data relevant to the learning and cognitive processes of university subjects. The aim of the study is to develop computer-based prototypes that simulate the processes of solving intellectual problems. These simulations help to deepen the understanding of such processes and to extract maximum information for future professional development and the construction of intelligent systems. Another key objective of artificial intelligence is to facilitate the execution of tasks characterized by a large number of variables, high complexity, and low suitability manually is systematized. The novelty of the study suggests in the personalization of the educational process for the learner, the application of adaptive cognitive learning strategies, and the incorporation of intelligent feedback mechanisms. The proposed model stands out from others due to the inclusion of components such as machine learning, intelligent tutoring systems, automated assessment systems, and large-scale data analysis. The article shows the possibilities of using AI to enhance engagement of students in forecasting their academic success and optimizing administrative processes. It also substantiates the need for the responsible use of AI in educational platforms, the development of integration strategies, and the assurance of fair access to resources.